2020
DOI: 10.1186/s42269-020-00294-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sublethal doses of some insecticides and their role on detoxication enzymes and protein-content of Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae)

Abstract: Background: The indiscriminating and intensive use of insecticides to control the cotton leafworm (CLW), Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae), usually induces high levels of resistance. The insecticides are the principal method for controlling this pest because of its critical role in reducing insects when the economic threshold (ETL); therefore, the effectiveness of these insecticides should be maintained. So, the target of the present work was directed to focus on studying the change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Detoxification enzymes occur naturally in various biological processes, functioning on the target sites to neutralize various toxins prevalent in the insect body ( Lin et al, 2015 ; Bhandari et al, 2021 ; Siddiqui et al, 2022 ). According to some previous studies, the biochemical characterization of insect resistance to pesticides is connected to pesticide sensitivity at the target site and pesticide detoxification by metabolic enzymes (acetylcholinesterase, carboxylesterase, glutathione S-transferase, and cytochrome P450) ( Wu et al, 2014 ; Ismail, 2020 ; Yang et al, 2021 ; Siddiqui et al, 2022 ). These enzymes are crucial in detoxifying xenobiotics ( Hu et al, 2014 ), where their hosts can utilize these enzymes as biological indicators during pesticide detoxification ( Khan et al, 2021 )—for instance, Zhang et al (2016) reported that detoxification enzymes (cytochrome P450 genes) were detected during detoxification of fipronil in the red imported fire ants ( Solenopsis invicta Buren), where up to 36.4-fold rise in resistance was recorded following exposure of the ants to fipronil.…”
Section: Molecular Mechanisms By Which Enzymes Mediate Pesticide Deto...mentioning
confidence: 99%
“…Detoxification enzymes occur naturally in various biological processes, functioning on the target sites to neutralize various toxins prevalent in the insect body ( Lin et al, 2015 ; Bhandari et al, 2021 ; Siddiqui et al, 2022 ). According to some previous studies, the biochemical characterization of insect resistance to pesticides is connected to pesticide sensitivity at the target site and pesticide detoxification by metabolic enzymes (acetylcholinesterase, carboxylesterase, glutathione S-transferase, and cytochrome P450) ( Wu et al, 2014 ; Ismail, 2020 ; Yang et al, 2021 ; Siddiqui et al, 2022 ). These enzymes are crucial in detoxifying xenobiotics ( Hu et al, 2014 ), where their hosts can utilize these enzymes as biological indicators during pesticide detoxification ( Khan et al, 2021 )—for instance, Zhang et al (2016) reported that detoxification enzymes (cytochrome P450 genes) were detected during detoxification of fipronil in the red imported fire ants ( Solenopsis invicta Buren), where up to 36.4-fold rise in resistance was recorded following exposure of the ants to fipronil.…”
Section: Molecular Mechanisms By Which Enzymes Mediate Pesticide Deto...mentioning
confidence: 99%
“…Resistance and detoxification of pesticides and many more (Ismail, 2020;Clark et al, 2021;Ahmad et al, 2022b;Siddiqui et al, 2022). Insect pests' resistance against different pesticides by insect gut microbial enzymes was reported (Table 2).…”
Section: Aedes Aegypti Ddt and Deltamethrinmentioning
confidence: 99%
“…Besides, it can reduce the photosynthetic area and growth rate of more than 100 plant species in 40 families as a leaf feeder and cutworm on seedlings and bolls (Pluschkell et al ., 1998; Darvishzadeh, 2014). The use of synthetic insecticides, a common strategy to control S. littoralis , has led to the development of insecticide-resistant insects (Wei et al ., 2018; Ismail, 2020). The long-term use of pesticides also has a negative effect on the environment, natural enemies of the pest, and human health (Le et al ., 2010; Radwan et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%